2018
DOI: 10.1016/j.psychres.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability and feasibility of a novel virtual reality based social skills training game for schizophrenia: Preliminary findings

Abstract: Social impairment is a core feature of schizophrenia that presents a major barrier toward recovery. Some of the psychotic symptoms are partly ameliorated by medication but the route to recovery is hampered by social impairments. Since existing social skills interventions tend to suffer from lack of availability, high-burden and low adherence, there is a dire need for an effective, alternative strategy. The present study examined the feasibility and acceptability of Multimodal Adaptive Social Intervention in Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 70 publications
(72 reference statements)
1
74
1
2
Order By: Relevance
“…Regarding the clinical symptoms of patients, VRT has been applied in rehabilitation of schizophrenia and showed effect on relieving the symptoms. A study showed patients with schizophrenia exhibited a signi cant reduction in overall clinical symptoms 10 sessions of VR training (33), and social function improved after a VR interview training (34). But in our study, we found VRT only improved the general psychopathology symptoms in patients rather than positive symptoms or negative symptoms.…”
Section: Discussioncontrasting
confidence: 77%
“…Regarding the clinical symptoms of patients, VRT has been applied in rehabilitation of schizophrenia and showed effect on relieving the symptoms. A study showed patients with schizophrenia exhibited a signi cant reduction in overall clinical symptoms 10 sessions of VR training (33), and social function improved after a VR interview training (34). But in our study, we found VRT only improved the general psychopathology symptoms in patients rather than positive symptoms or negative symptoms.…”
Section: Discussioncontrasting
confidence: 77%
“…Moreover, they found that social skills, communication, and cognitive skills improved with the AR usage [50]. The benefits of using clinical XR are apparent in studies showing that practicing difficult (or individually challenging) social interactions leads to less-anxiety [51,52]. Through the simplification and structuration of everyday social skills, patients can practice social interactions (i.e., finding another to sit with in a classroom) without the anxiety levels and/or fears of rejection that commonly accompany real-world social interactions.…”
Section: Clinical Xr: Structuring Multisensory Bodily Contentsmentioning
confidence: 99%
“…VR technology has been of interest to the psychiatric community as the ability to simulate real‐world situations in a controlled environment holds potential in supporting the therapy of various psychiatric conditions (Freeman et al, 2017). Already, the use of VR has been trialled on patients with post‐traumatic stress disorder (PTSD) (McLay et al, 2014), schizophrenia (Adery et al, 2018) and Internet addiction (Zhang & Ho, 2017). While results of studies assessing the efficacy of VR exposure therapy on phobias (Wechsler, Kümpers, & Mühlberger, 2019), PTSD (Deng et al, 2019) and anxiety disorders (Powers & Emmelkamp, 2008) have previously been combined in meta‐analyses, no such analysis has been done on the topic of eating disorders (ED).…”
Section: Introductionmentioning
confidence: 99%